Detection of Breast Cancer Using Some Parameters with ELAISA Technique in Patients Al-Najaf Al-Ashraf - Hashym, Qassim. M.; Almosawi, Sadeq Mohammad Jaafar (Medical Science Journal for Advance Research, 2026)
Background: Binding of GATA proteins is among the six members of a transcription factor family. Contributing to the luminal differentiation of breast epithelium, alongside the development of the collecting system and The process of trophoblastic differentiation. Methods: The present study collected 160 blood samples, which were divided into two groups. The first group consisted of healthy women (40), while the second group comprised patients with breast cancer (120 women). Results: ELAISA techniques were employed to assess the prognosis of breast cancer based on serum parameters associated with immuno gene transcriptions. The immunomodulatory GATA, binding protein 3, is recognized as a transcription" factor that is significant in the differentiation of breast epithelial cells. Additionally, interleukin-37 (IL-37) ,alternatively designated as Interleukin-1 family member-7, (IL-1F7), is an anti-inflammatory cytokine that is critical for the attenuation of start-inflammatory cytokine synthesis and the inhibition of cancer cell growth. The statistical analysis of the immune markers (GATA3 and IL-37) indicated a significant relationship with cancer when comparing the 120 samples collected from patients to the 40 samples from healthy individuals. The results were highly significant, with a p-value of <0.004, in Najaf Al-Ashraf. Conclusion: All immune markers indicate the presence of cancer in the body, which confirmed the clinical signs that were verified, such as redness and breast spotting, which were closely associated with the disease.